1994
DOI: 10.1111/j.1365-2222.1994.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity pneumonitis induced by Penicillium expansum in a home environment

Abstract: An episode of fever, cough, shortness of breath and leucocytosis developed in a 31-year-old atopic housewife from mould exposure in her home environment is evaluated. A chest radiograph revealed diffuse tiny nodular infiltrations in both whole lung fields. Spirometry revealed a severe restrictive type of ventilation impairment. Bronchoalveolar lavage (BAL) showed an increased lymphocyte count with reversed CD4+/CD8+ ratio and transbronchial lung biopsy showed markedly increased lymphocytic infiltration in alve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…In BAL fluid from a 31-year old atopic housewife exposed to Penicillium expansum, Park et al [4] found an increased lymphocyte count with reversed CD4 þ /CD8 þ ratio, supporting the findings of our study.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…In BAL fluid from a 31-year old atopic housewife exposed to Penicillium expansum, Park et al [4] found an increased lymphocyte count with reversed CD4 þ /CD8 þ ratio, supporting the findings of our study.…”
supporting
confidence: 94%
“…There are a few case reports in the literature of persons exposed to moulds in their home environment with diagnosed hypersensitivity pneumonitis [3,4]. In BAL fluid from a 31-year old atopic housewife exposed to Penicillium expansum, Park et al [4] found an increased lymphocyte count with reversed CD4 þ /CD8 þ ratio, supporting the findings of our study.…”
supporting
confidence: 93%
“…In indoor-air exposure, only sporadic cases of alveolitis have been reported in Finland (71). In other countries, a few cases of alveolitis caused by Penicilliunz species have been reported, along with sporadic cases caused by yeasts, such as Spovobolomyces and Rhodotorula (72)(73)(74). In some cases, the findings have not met all the classical diagnostic criteria of alveolitis.…”
Section: Alveolitis and Organic Dust Toxic Syndromementioning
confidence: 85%
“…Reports of acute mold-related HP include children exposed to an unventilated shower contaminated with Epicoccum nigrum [2], a housewife exposed to Penicillium expansum contaminated wood dust [3], the inhalation of basidiospores during processing and packing of mushrooms [4], and an adult who developed HP caused by Pezizia domiciliana after house flooding from the rains of El Niño [5]. Species of Aspergillus have been implicated in a soy sauce brewer, a farmer with a poorly ventilated greenhouse, a hospitalized patient inhaling contaminated humidified oxygen [6], and Spanish stucco makers working with moldy esparto grass fibers [7].…”
Section: Fungal Antigens Of Hypersensitivity Pneumonitismentioning
confidence: 99%